The Role and Importance of the Caries Detectors Dyes in Early Diagnosis and Treatment of Dental Caries - Pancu Galina; Stoleriu Simona; Andrian Sorin; Gheorghe Angela; Topoliceanu Claudiu; Pancu Ion; Lacatusu Stefan (Romanian Society of Oral Rehabilitation, 2010)
Despite the progresses of the modern dentistry, the carious disease is still affecting a large number of peoples. The caries detectors would be helpful for diagnosis of early enamel caries as well as dentinal caries. The study focused on the role of caries detectors on objective criteria of assessment of the caries preparation, the early diagnosis of the incipient caries as well as monitorisation of the remineralising processes. The study used product Color-test of the Vladmiva (Rusia): solution and gel. The study was performed on 25 patients age 15-38 with medium and high level of cariogenic status. The statistical results show the practical importance of the caries detectors for the conservative treatment of the dental caries, with different degree of penetration in dental tissues. It also allows the monitorisation of the success of the non-invasive or minimal invasive treatment. The use of the caries detectors allows minimal preparation of the dental issues, accordingly to modern principles of the actual dentistry.